Web site design & its implications in learning - Lim, Florence Yen Ling. (2008)
The purpose of this paper is to consider design aspects that can help improve instructional effectiveness of teaching and learning through the World Wide Web and to provide designers and educators with the ideas to increase the usability and appeal of web sites.